DEVElOPMENT OF INTERMEDIATE MOISTURE MARINATED FISH PRODUCT AND ITS STORAGE CHARACTERISTICS - Mandal, Sagar C.; Basu, S. (Journal of Indian Fisheries Association, 2008)
An attempt was made to prepare an intermediate moisture (around 44% moisture) marinated (pH around 4) fish product. Fillets from Sdaenid fish (each fish weighing 70-80 gm) were dipped in a solution containing 7% acetic acid, 20% common salt and 1% propionic acid for 2 hours. After soaking, the soaked fillets were partially dried to about 44% moisture. Three effective hurdles like low pH by using 7% acetic add and 1% propionic acidL low water activity (by using 20% salt and partially drying the fillets) and preservative (1% propionic add), were used to prepare a shelfstable product at room temperature. The dried product was sprayed with 0.05% BHA in 50% alcohol and further dried for 10 minutes to remove added water and alcohol, thereby another hurdle preservative against fat oxidation. The product was packed in 300 gauge polythene bags and stored in transparent screw cap plastic jars. Fortnightly samples were drawn and subjected to biochemical, bacteriological and organoleptic evaluation to study its storage characteristics. The product was in good acceptable form up to 4 months at ambient temperature. The product needed one hour soaking in water with two changes of water in between to make it free from excess salt and acid smell. Key words: Intermediate moisture, fish product, marinated fish product, storage life, hurdle technology.